Anyag Multi-Purpose Cooperative - Castellano, Victoria Alexis; Congcong, Angel; Mopia, Princess Liza Lo.; Ramos, Yvony Joy.; Rojo, Lea.; Taghap, Ralyn; Velarde, Rowena (2016)
Executive summary-This business plan is made for women residents of Brgy, Dapdap, Tigbauan, province of Iloilo who are members of their local women's cooperative. These women belong to families or those who have been actively participating in the Local Council of Women in their community. The company name is Anyag Multi-Purpose cooperative, or simply called Anyag. It is a produce and marketing cooperative of Dapdap, Tigbauan. Anyag promotes the willingness and the hard-working capabilities of these women in order to produce their main product, which are the Chipioca Cassava Crackers. The whole idea of Anyag of selling these Chipioca cassava crackers is that it is not just the usual profit-gaining cooperative. Every product of Anyag has its own story, which is told by our company's tagline. With every purchase of a product from Anyag, specifically Chipioca cassava crackers, every Peso they earn, every chip/cracker they sell to people, the lives of these women workers are improved even in the simplest way possible. Anyag envisions itself to be well-known as a producer and distributor of a different kind of snack of the Ilonggo community and the Philippines.
Business Plan ( Mgt 191-Entrepreneurial Management). -- [Iloilo City] : UPV-CM, April 2016.